2018
DOI: 10.18544/pedm-24.01.0101
|View full text |Cite
|
Sign up to set email alerts
|

Polycystic ovary syndrome (PCOS) and the accompanying disorders of glucose homeostasis among girls at the time of puberty

Abstract: Polycystic ovary syndrome (PCOS) usually arises during puberty and is marked by insulin resistance, hyperinsulinemia, and hyperandrogenism. The principle is that the diagnosis of PCOS must be based on the presence of at least two of the following three criteria: chronic anovulation, hyperandrogenism (clinical or biological), and polycystic ovaries. The diagnosis of PCOS in adolescents is particularly difficult due to developmental problems in this group. Many symptoms of PCOS, including acne, menstrual irregul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…Insulin resistance is the central mechanism linking together all parameters of the metabolic syndrome, such as: impaired glucose tolerance (IGT), type 2 diabetes mellitus (DMT2), hyperlipidemia and cardiovascular disease over-time [3−5]. Adolescent girls with PCOS have been shown to have early-onset insulin hypersecretion in association with insulin resistance [2], and approaches for reversal of severe hyperinsulinemia early in its course, prevented them from developing health problems later in life, such as diabetes, cardiovascular disease and infertility [6].…”
Section: Prevalence and Predictors Of Impaired Glucose Tolerance And Diabetes Mellitus Type 2 In Patients With Polycystic Ovary Syndromementioning
confidence: 99%
“…Insulin resistance is the central mechanism linking together all parameters of the metabolic syndrome, such as: impaired glucose tolerance (IGT), type 2 diabetes mellitus (DMT2), hyperlipidemia and cardiovascular disease over-time [3−5]. Adolescent girls with PCOS have been shown to have early-onset insulin hypersecretion in association with insulin resistance [2], and approaches for reversal of severe hyperinsulinemia early in its course, prevented them from developing health problems later in life, such as diabetes, cardiovascular disease and infertility [6].…”
Section: Prevalence and Predictors Of Impaired Glucose Tolerance And Diabetes Mellitus Type 2 In Patients With Polycystic Ovary Syndromementioning
confidence: 99%
“…The maintenance or progression of these symptoms over a longer period of observation, as well as disturbances in the metabolic profile of patients (not included in the criteria for the diagnosis of PCOS) are also of great importance. Obesity and metabolic disorders should be included in the diagnostic and therapeutic process in girls with suspected PCOS not only as components of this syndrome, but primarily as risk factors for diabetes, cardiovascular diseases and infertility later in life (Otto-Buczkowska et al, 2018). Research by Polish authors (Drosdzol-Cop, Tymińska-Bandoła, Bil, Stojko, Skrzypulec-Plinta, 2017) showed that up to 80% of girls with PCOS were overweight or obese.…”
Section: Hyperandrogenism and Pcos-related Metabolic Disorders In Adolescentstherapeutic Optionsmentioning
confidence: 99%
“…The level of inflammatory factors in patients with PCOS is often positively correlated with the level of androgen (Spiller et al, 2014;van Rooijen and Sanders, 1994). The levels of inflammatory factors such as TNF-α, IL-6 and MCP-1 in serum of patients with PCOS are increased, which is positively correlated with the concentration of testosterone in serum (Escobar-Morreale, 2018;Otto-Buczkowska et al, 2018).…”
Section: Introductionmentioning
confidence: 99%